The 2019 Nigerian presidential elections and the resurgence of the magic bullet theory of media effect - Patrick Ene Okon; Joseph Enyia Ekpang II (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
This study examined the continued relevance of Magic Bullet Theory, also called Hypodermic Needle Theory. It adopted the applied and survey research methods. The sample had 1,265 respondents. Qualitative analytical approach was used to discuss how the Magic Bullet Theory has remained a relevant interpretative tool for assessing the behaviour of media audiences during election period. Theoretical framework was anchored on Tichenor, Donohue and Olien’s Knowledge Gap Theory. The paper argued that the impactful use of media propaganda (particularly fake news on social media) during Nigeria’s 2019 elections has demonstrated the continued relevance of the theory in media studies, especially as it was observed that members of the main competing parties and aides of election contestants used fake news on social media to influence voters’ electoral judgments. Internet-based rumours of President Muhammadu Buhari’s demise and his “Islamisation” agenda, for instance, created such great concern that his party, the All Progressive Congress, exerted much efforts during its campaigns to debunk these allegations. Findings from the study led to the conclusion that media content substantially influenced the voters’ choice on who to support; and this vividly showed in the party’s dismal electoral performance in the Christian-dominated South-East, South-South and North-Central geo-political zones.